Integrating User-Centred Design Approaches for a Course Design Framework for Interdisciplinary Studies Teaching and Learning - Yasushi Akiyama; Sharon Woodill (University of Windsor, 2020)
This paper proposes the theoretical context for a course development framework to address the specific needs and challenges of teaching and learning in Interdisciplinary Studies (IDS). User-Centred design (UCD) principles are used for this development process. Traditional course development frameworks provide a helpful guide in terms of setting out the steps necessary for successful course development. While these steps will inform the course development framework being proposed here, several alterations will be made. The unique demands of teaching and learning in IDS require skill development necessary for doing advanced interdisciplinary work and eschews linearity. The key feature of this framework is the inclusion of intentional iterative phases throughout course delivery that will allow for adaptation based on the incorporation of feedback in a variety of forms: self, instructor, peer, stakeholder (e.g., from service-learning supervisors), and cognitive skills assessment tools. The adaptive nature of this framework should meet the demands of the growing area of IDS.